Opioid Use Patterns After Nonsurgical Management of Distal Radius Fractures: A Call for Opioid Stewardship - Sina Ramtin, MD; Sara Khan, BS; Vijay Chhabra, BA; Wali Pirzada, BS; Mohammad Khak, MD; Asif M. Ilyas, MD, MBA (Journal of Hand Surgery Global Online)
Purpose: While most opioid research focuses on postoperative use, limited data exist on prescribing patterns in nonsurgical management of common injuries such as distal radius fractures (DRFs). This study aimed to assess opioid prescribing trends and identify factors linked to prolonged use in nonsurgically treated DRFs. Methods: A retrospective cohort study of 591 patients aged 18–50 with nonsurgically managed DRFs between 2018 and 2024 was conducted. Opioid use was classified as prior opioid use (POU), fracture-related opioid use (FxOU), or delayed opioid use (DOU). Prescription data were obtained from the Prescription Drug Monitoring Program and analyzed for morphine milligram equivalents, number of prescriptions, prescriber type, and timing relative to orthopedic consultation. Results: Only 32% of patients received an opioid prescription after their DRF. Among the 189 who did, 35% were POU; 37% were FxOU, and 28% were DOU. Orthopedic surgeons prescribed opioids in just 6% of total cases and 19% of cases among opioid recipients; 81% of prescriptions came from nonorthopedic providers. Surgeons wrote only 11% of FxOU prescriptions, whereas 56% of POU and DOU prescriptions were from nonorthopedic prescribers. Patients with POU had significantly higher cumulative morphine milligram equivalents compared with those with FxOU. No significant morphine milligram equivalent or prescription count difference was found between surgeons and nonorthopedic prescribers, but patients with DOU had a higher prescription count. Conclusions: Most patients with nonsurgical DRFs did not receive opioids. When prescribed, over 80% of opioids originated from nonorthopedic providers. Delayed opioid use and POU were associated with increased cumulative exposure, highlighting the need for fracture surgeons to take a more active role in opioid stewardship and for improved coordination across providers to reduce unnecessary opioid exposure. Type of study/level of evidence: Prognostic II.